The Modification of Sodium Polyacrylate Water Solution Cooling Properties by AL2O3 - Wojciech Gęstwa; Małgorzata Przyłęcka (Advances in Materials Science and Engineering)
This paper presents a preliminary examination of water cooling ability as a result of its modification by the addition of sodium polyacrylate and AL2O3 nanoparticles. (AL2O3) alumina oxide was present in gamma phase as a form of nanopowder whose particle size was less than 50 nm. Cooling curves in the temperature-time system were marked for the three cooling media: water, 10% water solution of sodium polyacrylate, and 10% water solution of sodium polyacrylate with 1% addition of AL2O3 nanoparticles. Based on cooling curves, it can be concluded that for the water solution of sodium polyacrylate with AL2O3 nanoparticles in comparison to water and 10% polymer water solution lower cooling speed is obtained. The cooling medium containing nanoparticles provides lower cooling speed in the smallest surface austenite occurance (500–600 C) in the charts of the CTP for most nonalloy structural steels and low-alloy steels. However lower cooling temperature at the beginning of martensitic transformation causes the formation of smaller internal stresses, leading to smaller dimensional changes and hardening deformation. For the quenching media the wetting angle was appointed by the drop-shape method. These studies showed the best wettability of polymer water solution (sodium polyacrylate) with the addition of AL2O3 nanoparticles, whose wetting angle was about 65 degrees. Obtaining the smallest wetting angle for the medium containing nanoparticles suggests that the heat transfer to the cooling medium is larger. This allows slower cooling at the same time ensuring its homogeneity. The obtained values of wetting angle confirm the conclusions drawn on the basis of cooling curves and allowus to conclude that in the case of the heat transfer rate it will have a lower value than for water and 10% polymer water solution. In the research on hardened carburized steel samples C10 and 16MnCr5 surface hardness, impact strength and changes in the size of cracks in Navy C-ring sample are examined. On this basis of the obtained results it can be concluded that polymer water solution with nanoparticles allows to obtain a better impact strength at comparable hardness on the surface. Research on the dimensional changes on the basis of the sample of Navy C-ring also shows small dimensional changes for samples carburized and hardened in 10% polymer water solution with the addition of nanoparticles AL2O3. Smaller dimensional changes were obtained for samples of steel 16MnCr5 thanfar C10. The results allowus to conclude that by the addition of solid nanoparticles to water based quenching media their cooling properties which are not inferior to mineral oils and polymer water solutions can be shaped.